Pengaruh Statistik Inferensial dalam Pengambilan Keputusan Investasi - Margana, Marina Silvya; Aziz Ramdhani, Muhammad Abdul; Gitsni, Muhammad Faizal; Haikal Kamil, Muhammad Rizki; Sandrina, Nahla Galuh; Wardiyah, Mia Lasmi (Melati Institute, 2024)
The application of inferential statistics in investment decision-making is a critical step in the world of modern finance. This research aims to explore how inferential statistical methods, such as regression, analysis of variance (ANOVA), and hypothesis testing, can be used to identify profitable investment opportunities and manage risk. Through case studies and historical data analysis, this research demonstrates that the use of inferential statistics can improve prediction accuracy and provide a stronger basis for investment decision-making. The results of this study are expected to provide insights for investors and portfolio managers in designing more effective investment strategies. Translated with DeepL.com (free version)